Effect of Paracervical Block Before Ultrasound Guided High Intensity Focused Ultrasound Treatment in Uterine Fibroids and Adenomyosise - Jae-Seong Lee; Kye-Hwa Lee; Tae-Eung Kim (IMR Press, 2022)
Background: The purpose of this article was to evaluate the effect of paracervical block before ultrasound-guided high-intensity-focused ultrasound treatment of adenomyosis and uterine fibroids. Methods: This retrospective analysis examined 2173 women who received HIFU treatment for uterine fibroids and adenomyosis, among them 311 patients with paracervical block and 1862 patients without paracervical block, from February 4, 2010 to March 8, 2019. We assessed treatment time, ablation time, treatment energy and volume reduction. Paracervical block (10 cc of 2% lidocaine diluted with epinephrine 1:1 million) was performed before treatment. Results: When paracervical block was performed, the total treatment time was estimated to be 0.886 times (expected (-0.121)) which was statistically significantly shorter (p < 0.0001), ablation time was statistically significantly shorter by 0.853 times (expected (-0.159)) (p < 0.0001), and the total energy was statistically significantly smaller by 0.891 times (expected (-0.115)) (p = 0.0003). There was no significant difference in volume change between the group with and without paracervical block. However, total treatment time, ablation time, and treatment energy were all statistically significantly lower in the group treated with paracervical block. Conclusions: Paracervical block before USgHIFU treatment was a cost-effective method because it helped reduce the total treatment time, ablation time, and total energy.